SPECIFIC ANTIDOTES TO NEW ORAL ANTICOAGULANTS - O. O. Shakhmatova («REMEDIUM GROUP» Ltd., 2016)
Safety profiles of the novel oral anticoagulants (NOAC) (rivaroxaban, apixaban, edoxaban,  dabigatran) are better than that of warfarin. However, the risk (including lifethreatening) of bleeding  is no less than 2.3-3.1% per year. Three specific antidotes  to NOAC are currently  in different phases of clinical  trial and implementation. Idarucizumab  is a monoclonal  antibody which immediately and completely  reverses the anticoagulation effect of dabigatran. Andexanet  alfa is a recombinant, modified factor Xa molecule  that binds and inhibits the effects of oral and parenteral factor Xa inhibitors  (rivaroxaban, apixaban,  edoxaban, fondaparinux, heparins).  Andexanet  is already in 3b Phase, and at the end of 2016  - beginning  of 2017 it is expected  to be approved  for clinical  use. Ciraparantag  is a small molecule,  non-covalently binding to factor Xa inhibitors, and dabigatran  (i.e., a universal  antidote).  Recently, promising results of phase 1 trials involving aripazin were published. The article  tells about the practical  aspects of the use of antidotes, treatment  approaches for life-threatening bleeding  during treatment  with NOAC.